Microestructure, chemical composition and mucilage exudation of chia (Salvia hispanica L.) nutlets from Argentina - Capitani, Marianela Ivana (2013)
The micromorphology and anatomy of nutlets, myxocarpy (mucilage exudation) and mucilage structure of Argentinean chia were described using scanning electron microscopy (SEM). The proximal composition of nutlets and mucilage was also studied. RESULTS: Chia nutlets are made up of a true seed and a pericarp enclosing the seed; they are small, glabrous, elliptic and apically rounded. The pericarp has cuticle, exocarp, mesocarp and bone cells vertically arranged and endocarp. The myxocarpy was carefully recorded by SEM. After 5 min in contact with water, the cuticle of nutlets is broken and the exocarp cell content gradually surrounds the rest of the nutlet. The proximal composition of chia nutlets was studied; fat is the major component (327 ±8.0 g kg−1) followed by protein (293 ±4.0 g kg−1) and ﬁber (276 ±1.0 g kg−1). Extractions of chia nutlets with water at room temperature yielded 38 ±1.0 g kg−1 (dry basis) of mucilage. The fresh mucilage structure was similar to a network of open pores. The freeze-dried crude mucilage contained more ash, residual fat and protein than commercial guar and locust bean gum. The solubility of 10.0 g L−1 w/v solution of chia freeze-dried crude mucilage in water increased with temperature, being maximal at 60 ◦C (870 g kg−1. CONCLUSION: The results obtained show a fast exudation of chia mucilage when nutlets are in contact with water. The freeze-dried crude mucilage hydrates easily in water, even at low temperatures. Chia nutlets have mucilaginous substances, with interesting functional properties from a technological and physiological point of view.